2016
DOI: 10.1186/s12879-016-1703-z
|View full text |Cite
|
Sign up to set email alerts
|

Switching to boosted protease inhibitor plus a second antiretroviral drug (dual therapy) for treatment simplification: a multicenter observational study

Abstract: BackgroundAim of the study was to assess predictors of discontinuation/toxicity of boosted PI-based (PI/r) dual therapy (DT).MethodsObservational, retrospective switch study in patients successfully treated with triple drugs regimen. Patients switched to PI/r based DT [darunavir (DRV/r), lopinavir (LPV/r) or atazanavir (ATV/r)] plus a second drug: [raltegravir (RAL), maraviroc (MVC) etravirine (ETR), lamivudine (3TC) or tenofovir (TDF)] between 2009 and 2014 were included. The effect of each drug as well as ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…In the last few years, the use of 2DRs has gradually taken place as a novel paradigm for the treatment of HIV infection. Initially, 2DRs have become feasible due to the availability of last-generation boosted PIs, which are characterized by a high potency and genetic barrier; several trials and studies from clinical practice have demonstrated the efficacy and durability of 2DRs based on a PI plus a second drug for the treatment of HIV infection [37][38][39][40][41][42]. The advent of InSTIs, which are characterized by improved tolerability relative to PIs, has prompted researchers to evaluate the efficacy of InSTI-based 2DRs, especially those including dolutegravir, a second-generation InSTI with a high genetic barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, the use of 2DRs has gradually taken place as a novel paradigm for the treatment of HIV infection. Initially, 2DRs have become feasible due to the availability of last-generation boosted PIs, which are characterized by a high potency and genetic barrier; several trials and studies from clinical practice have demonstrated the efficacy and durability of 2DRs based on a PI plus a second drug for the treatment of HIV infection [37][38][39][40][41][42]. The advent of InSTIs, which are characterized by improved tolerability relative to PIs, has prompted researchers to evaluate the efficacy of InSTI-based 2DRs, especially those including dolutegravir, a second-generation InSTI with a high genetic barrier.…”
Section: Discussionmentioning
confidence: 99%
“…None of the trials of two‐drug combinations have studied the effect of treatment simplification on HIV tissue reservoirs. Only one has looked at the effect of treatment simplification on blood reservoirs in terms of total HIV DNA, although measurements of the replication competent reservoir would have been more relevant .…”
Section: The Issue Of Inflammation and Immune Activationmentioning
confidence: 99%
“…Com o desenvolvimento de inibidores de integrase mais potentes, houve um aumento do número de estudos que avaliam o uso da terapia dupla em pessoas vivendo com HIV, os quais têm demonstrado efetividade da terapia dupla na manutenção da carga viral indetectável (Mondi et al, 2015;Latini et al, 2016;Fabbiani et al, 2016;Perez-Molina et al, 2017;Pulido et al, 2017;Fabbiani et al, 2018). Contudo, os eventos adversos provocados pelo consumo desses medicamentos são uma das maiores causas de descontinuação do tratamento.…”
Section: Discussionunclassified